(untitled) (Experimental biology, 2023)
A characteristic feature of wetlands in the Ili River delta is the predominance of common reed (Phragmites australis) in the composition of their plant communities. Reedbeds are ecologically valuable ecosystems that play an important role in the nutrient cycle, carbon sequestration, oxygen production and maintenance of biodiversity. Ecosystems in the Ili delta provide a wide range of ecosystem services and have been used by people for economic purposes for centuries. The main types of ecosystem services of reed wetland communities in the delta were investigated and various options for the management of reed communities were analyzed, the existing complexities and conflict potential between biodiversity conservation and the established economic activities of the local population and visitors were described. Some innovative options for more effective and sustainable use of reed biomass for economic purposes and ways of optimal management of reed cenoses, considering their functional importance for biodiversity, are proposed.